2021
DOI: 10.1177/2192568221998371
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Rod Contouring to Desired Angles With and Without a Template: Implications for Achieving Desired Spinal Alignment and Outcomes

Abstract: Study Design: Biomechanical Study. Objective: The search for optimal spinal alignment has led to the development of sophisticated formulas and software for preoperative planning. However, preoperative plans are not always appropriately executed since rod contouring during surgery is often subjective and estimated by the surgeon. We aimed to assess whether rods contoured to specific angles with a French rod bender using a template guide will be more accurate than rods contoured without a template. Methods: Ten … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Various factors have been implicated in thoracic hypokyphosis and reciprocal loss of lumbar lordosis after AIS surgery. They include: The surgeon themselves: Variation in surgeons’ choice of techniques and differences between different surgeons’ techniques, including variation in rod contouring [ 12 , 25 , 26 , 27 , 28 , 29 , 30 ]. Implant density and implant choice: Higher screw density on the concave side with thicker and cobalt chrome rods have been associated with restoration of kyphosis to greater than 20 degrees [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various factors have been implicated in thoracic hypokyphosis and reciprocal loss of lumbar lordosis after AIS surgery. They include: The surgeon themselves: Variation in surgeons’ choice of techniques and differences between different surgeons’ techniques, including variation in rod contouring [ 12 , 25 , 26 , 27 , 28 , 29 , 30 ]. Implant density and implant choice: Higher screw density on the concave side with thicker and cobalt chrome rods have been associated with restoration of kyphosis to greater than 20 degrees [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The surgeon themselves: Variation in surgeons’ choice of techniques and differences between different surgeons’ techniques, including variation in rod contouring [ 12 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the operating room, rods are bend manually using French benders, which may cause over or under bending of the rods and lead to malalignment. Biomechanical properties of posterior instrumentation and rod contouring are important factors effecting the patient outcomes (6,7). Adequate rod contouring is vital for achieving both global and regional target re-alignments, thus, reinforcing the importance of intra-operative rod bending.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that inappropriate (over or under) bending of spinal rods can affect the postoperative spino-pelvic alignment, leading to inferior patient outcomes (6).…”
Section: Introductionmentioning
confidence: 99%